2016
DOI: 10.5152/tpd.2016.4211
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Hypereosinophilia: A Case Report

Abstract: Toxocariasis is a parasitic disease caused by the larval stage of Toxocara cati and T. canis, which live in the intestinal system of cats (T. cati) and dogs (T. canis). Infective eggs can enter the gastrointestinal system by the oral route via foods contaminated with feces of dogs or cats or via dirty contaminated hands. The larvae penetrate the small intestine and migrate to visceral organs by systemic circulation. Hypereosinophilia is a common finding in the tissue invasion of parasites. Serological methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Various studies have suggested that geographical location, socioeconomical status, contact with soil, dog, and cat, age, sex, pica, and ingestion of raw cow liver or meat are the most important risk factors for acquiring the disease (Campos Júnior et al 2003;Fillaux et al 2007;Kwon et al 2017;Kwon et al 2011). Eosinophilia in peripheral blood occurs in allergic diseases and cancers and is commonly found in tissue-invading parasites (Merdin et al 2016;Won et al 2015); VLM is often complicated by blood eosinophilia (Van Den Broucke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have suggested that geographical location, socioeconomical status, contact with soil, dog, and cat, age, sex, pica, and ingestion of raw cow liver or meat are the most important risk factors for acquiring the disease (Campos Júnior et al 2003;Fillaux et al 2007;Kwon et al 2017;Kwon et al 2011). Eosinophilia in peripheral blood occurs in allergic diseases and cancers and is commonly found in tissue-invading parasites (Merdin et al 2016;Won et al 2015); VLM is often complicated by blood eosinophilia (Van Den Broucke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Visceral toxocariasis occurs preferentially in children from 1 to 4 years of age with a history of geophagy. Clinically, it is characterized by fever, pulmonary signs and symptoms, hepatosplenomegaly and leukocytosis with marked eosinophilia [11,12]. Cases of neurological alterations have been reported that are manifested by seizures, paralysis, epilepsy and sometimes cause death when the number of larvae in the central nervous system is high [13,14].…”
Section: Introductionmentioning
confidence: 99%